Securing Energy-Constrained UAV Communications Against Both Internal and External Eavesdropping - Gao, Ying; Tang, Hongying; Li, Baoqing; Yuan, Xiaobing (IEEE communications letters, 2021)
This letter investigates an unmanned aerial vehicle (UAV) enabled network where an energy-constrained rotary-wing UAV is employed as a mobile base station to serve multiple ground users (GUs), while the data transmission between the UAV and each GU faces security threats from both multiple external eavesdroppers (Eves) and other GUs that potentially act as internal Eves. To ensure the user fairness, we maximize the minimum average secrecy rate among all GUs via jointly optimizing the UAV's trajectory and transmit power as well as the user scheduling, subject to the constraint on the UAV energy budget. To this end, an iterative suboptimal algorithm is proposed by leveraging the block coordinate descent and successive convex approximation techniques. Simulation results are provided to demonstrate the efficacy of the proposed algorithm.